Investment and profits - Stubelj, Igor (Managing global transitions, 2014)
The purpose of the paper is to present the theoretical and empirical analysis of the causal relationship between company's investment and profits. Following the previous research findings that are not unanimous, we examined the causal relation between profits and investment both at the aggregate and at the industry level. The theory on the field allows us to define three basic theses: profits determine investment on the aggregate level or industry sectors level in a national economy, investment determines profits, and profits determine investment and investment determine profits. We used the Granger definition of causality and the Toda-Yamamoto procedure. Based on the results of the analysis, we can claim that investment determines profits in a national economy. At the industry sectors level there is the greatest support for a cause-and-effect relation in the direction from profits to investment. The results of our empirical analysis and contextual interpretation can help in identifying potential factors and barriers that hinder the effective functioning of the economic system. It is undisputed that investment and profits is extraordinarily important for the economic system and that the investment and profits relation is undeniably strong.
Keywords: industry; naložbe; dobički; vzročnost; sektor gospodarstva; investment; profits; causality